2011
DOI: 10.1007/s12035-011-8219-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Mesenchymal Stem Cells as a Proposed Therapeutic for Huntington’s Disease

Abstract: There is much interest in the use of mesenchymal stem cells/marrow stromal cells (MSC) to treat neurodegenerative disorders, in particular those that are fatal and difficult to treat, such as Huntington’s disease. MSC present a promising tool for cell therapy and are currently being tested in FDA-approved phase I–III clinical trials for many disorders. In preclinical studies of neurodegenerative disorders, MSC have demonstrated efficacy, when used as delivery vehicles for neural growth factors. A number of inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 106 publications
(112 reference statements)
0
51
0
1
Order By: Relevance
“…Secreted neuron growth factors such as nerve growth factor, BDNF, and glial cell line-derived neurotrophic factor also facilitate the recovery from Alzheimer's disease, Huntington's disease, Parkinson's disease, multiple sclerosis, and Krabbe's disease. 105 Evidence has shown that the MSC's ability to secrete cytokines is regulated by PI3K/Akt activity. SDF-1 has been shown to increase the secretion of cytokines by MSCs, and this effect is mediated by the PI3K/Akt pathway.…”
Section: The Pi3k/akt and Cytokine Production Of Mscsmentioning
confidence: 99%
“…Secreted neuron growth factors such as nerve growth factor, BDNF, and glial cell line-derived neurotrophic factor also facilitate the recovery from Alzheimer's disease, Huntington's disease, Parkinson's disease, multiple sclerosis, and Krabbe's disease. 105 Evidence has shown that the MSC's ability to secrete cytokines is regulated by PI3K/Akt activity. SDF-1 has been shown to increase the secretion of cytokines by MSCs, and this effect is mediated by the PI3K/Akt pathway.…”
Section: The Pi3k/akt and Cytokine Production Of Mscsmentioning
confidence: 99%
“…Although no fundamental treatment has been established for blocking or even delaying the progression of SCA symptoms, a biochemical approach using mesenchymal stem cells (MSCs) is currently being tested in clinical trials for SCA as well as for other nervous system diseases [18] such as multiple sclerosis [19] and spinal cord injury [20]. In a study using 14 cases of SCA patients [21], the intrathecal injection of umbilical cord MSCs could improve the movement ability and quality of daily life 1 month after the treatment, as evidenced by scores of the International Cooperative Ataxia Rating Scale (ICARS) and Activity of Daily Living Scale (ADL).…”
Section: Polyglutamine Diseasementioning
confidence: 99%
“…Hastalığın huntingtin genindeki poliglutamin ekspresyonundaki patolojiye bağlı olduğu ortaya konmuştur. Hastalık serebral korteks, bazal ganglion, hipokampus ve hipotalamusda nöronal hücre kaybı sonucu koreik hareketler, kavramsal karışıklık ve psikiyatrik bozukluklarla seyretmektedir 60,61 . Hastalığın belirgin bir tedavisi bulunmamaktadır bu nedenle kök hücre nakli çalışmaları bir umut oluşturmaktadır.…”
Section: Huntington Hastalığıunclassified